PENGARUH PENAMBAHAN TEMULAWAK (Curcuma xanthorriza) PADA PAKAN BUATAN TERHADAP PERTUMBUHAN IKAN BANDENG (Chanos chanos) - Ardi Setyo Prabowo; Benny Diah Madusari; Tri Yusufi Mardiana (Pena Akuatika Jurnal Ilmiah Perikanan Dan Kelautan, 2017)
This research was done in 5 may – 5 june 2015 in the Laboratory of brackish water of the Faculty of Fisheries, University of Pekalongan. The puspose of this research is to know the influence of the addition of curcuma on feed to the growth of milkfish. A research method used in the design of random complete with one factor which feed containing curcuma with four standard treatment consist of, A (control without given curcuma solution), B (curcuma solution with a dose of 4 g/kg feed), the C (curcuma solution with a dose of 8 g/kg feed), the D (curcuma solution with a dose of 12 g/kg feed. the results of research shows the average extra weight to the biomass of fish highest in the treatment doses temulawak 12 g/kg feed, is the absolute averaga improvement in biomass 1,97 grams. While the treatment doses temulawak 0 g the feed to mean the lowest is 0, 74 grams. The results of analysis of variance on the grow of milkfish seed biomass know that the calculate F value is greater than the F table 1% and 5%. Range of water temperature during the study between 24 – 30oC, the pH of the water ranged from 6-8 and the oxygen dissolved in water (DO) ranged from 3,9-5,6 ppm. Key Word : Milkfish, temulawak, Growth